EFEKTIVITAS PEMBERIAN JUS WORTEL TERHADAP INTENSITAS DISMENOREA PADA MAHASISWA KEBIDANAN UNIVERSITAS PASIR PENGARAIAN - Nana Aldriana; Rohimi (Maternity and Neonatal : Jurnal Kebidanan, 2021)
Dysmenorrhea is a condition of a woman who experiences pain during menstruation which has a bad effect and causes disturbances in carrying out daily activities because of the pain. The pain arises due to the presence of the hormone prostaglandin which makes the uterine muscle (womb) contract. If not handled properly, it can reduce the quality of life of women. Treatment of dysmenorrhea can be by giving carrot juice. The content of beta-carotene and vitamin E in carrots can provide analgesic and anti-inflammatory effects that can help block the formation of prostaglandins and overcome the increase in the hormone prostaglandin, which is a hormone that affects dysmenorrhea. This study aims to determine the effectiveness of giving carrot juice to the intensity of dysmenorrhea in midwifery students at Pasir Pengaraian University, Rambah Hilir District, Rokan Hulu Regency. This research method is quantitative analytic with pre-experimental research design with one group pre-test and post-test design. Collecting data using a checklist while data analysis using the T- Dependent test. The sample in this study amounted to 20 female respondents who experienced dysmenorrhea. The results of the data analysis of the average decrease in the intensity of dysmenorrhea before being given carrot juice was 3.65 with a standard deviation of 0.93 and a standard error of 0.20. In the measurement after giving carrot juice, the average pain intensity was 0.30 with a standard deviation of 0.47 and a standard error of 0.10. In conclusion, there was an effect of giving carrot juice to decrease the intensity of dysmenorrhea in midwifery students at Pasir Pengaraian University, Rambah Hilir District, Rokan Hulu Regency with (p value = 0.001). Suggestions for women who experience dysmenorrhea to be able to consume carrot juice. Because the administration of carrot juice can reduce the intensity of dysmenorrhea in women and can be used as an alternative therapy.